Extreme coexceedances in new EU member states’ stock markets - Christiansen, Charlotte; Ranaldo, Angelo (Journal of Banking & Finance, 2009)
We analyze the financial integration of the new European Union (EU) member states’ stock markets using the negative (positive) coexceedance variable that counts the number of large negative (large positive) returns on a given day across the countries. A similar analysis is performed for the old EU countries. We use a multinomial logit model to investigate how persistence, asset classes, and volatility are related to the coexceedance variables. We find that the effects differ (a) between negative and positive coexceedance variables (b) between old and new EU member states, and (c) before and after the EU enlargement in 2004, suggesting a closer connection of new EU stock markets to those in Western Europe.